Creatine supplementation: Implications for the competitive weightlifter - Flanagan, E. P. (Strength and Conditioning Journal, 2007)
This article briefly reviews research on the topic of creatine supplementation with special reference to issues of relevance for competitive weightlifters. The article is aimed at weightlifters and their coaches to increase their knowledge of the supplement in a manner specifically relating to their sport. Recommendations are made regarding creatine's specific effect on weightlifting performance, suitable loading practices for weightlifters, and supplementation's effect in body weight maintenance.